WASTE BANK MANAGEMENT ASSISTANCE TO IMPROVE THE COMMUNITY ECONOMY - Ahmad Bayu; Purwanto; Yeny Fitriyani; Achmad Labib (Khidmatan, 2022)
This study aimed to determine the community's attractiveness in managing waste in Jombong Hamlet, Patent, Dukun, and Magelang. This activity aims to reduce the accumulation of household waste so that there is no disaster and to utilize the waste with the creations and innovations of the surrounding community. The methods used are observation, interviews, and documentation. With the PAR (Participatory Action Research) approach, the service team views the existence of a waste bank as an essential asset for the community. The results show that waste bank management benefits the surrounding community; the environment becomes comfortable, beautiful, and green. This study concludes that household waste can benefit from the social, economic, and environmental aspects that positively impact the Jombong Hamlet Waste Bank.